Feasibility study of developing wind power projects in Iceland: An economic analysis - Jónasson, Smári (My University, 2008)
Wind power development world-wide has been fast in past decades and the need for renewable energy sources continues to increase. The wind turbine technologies have proven established and are more inexpensive than they were ten years ago. However, not a single wind turbine has been installed and connected to the Icelandic power system. This study thus aims at evaluating the feasibility of harnessing wind power in Iceland from a wide range of perspectives with focus on economic analysis. It could serve as a preliminary guide for those interested in developing such a project. First of all, meteorological and geographical data collection and analysis is required. The Icelandic wind atlas contained the information on the wind availability is used to identify three best locations of a small wind farm to be studied further. Wind data is used to approximate the annual energy production for a hypothetical wind farm of 10 wind turbines, 2 MW each. The expected annual energy production is highest at Rauðinúpur with 8000 MWh and a capacity factor of 46% which is exceptionally high for an on-shore wind farm. The thesis also reviews laws and regulations with regard to wind power development such as environment and taxes since they have strong influence on the feasibility of the project. The review shows that there are lacks of wind power specific legislations and public policy to encourage wind power. This would likely cause the delay and add cost to such a project. Technical issues such as wind technology and wind-grid integration issues with regards to the impacts of wind power on power system operation and power quality are discussed. Finally, the indispensable economic evaluation of the wind power project is performed using simple work sheet models. The key project evaluation methods used for the chosen locations of the wind farm include internal rate of return (IRR), present value (PV), benefit-to-cost (B/C) ratio, and payback time methods. Risk management related to such a project is also discussed. An important part of the economic evaluation is the sensitivity analysis of the economic results performed by varying different key techno-economic inputs of the projects, such as the investment cost, electricity price, interest rate, size of the wind farm, and so on. The sensitivity analysis shows that with large investment costs, presumably financed by loans, the effect of discount rate and electrical price are the principal factors that determine the feasibility of the project. It could be concluded that the feasibility of raising a wind farm in Iceland is rather low at the moment, although it is clear that possible changes in the electricity markets such as the introduction of a green certificate system or rising energy prices could make the investment in wind power more economically attractive. It should also be noted that to promote wind power in Iceland, pilot wind turbines could be constructed to stimulate research in the area and increase knowledge and experience in the field of wind power.
Keywords: Elkraftteknik; Electric power engineering